A public R&D resource allocation model for 5G mobile industry in Korea - Suwon Kim; Chan-gi Nam; Sangwoo Lee; Seongcheol Kim (International Telecommunications Society (ITS), 2017)
5G needs to be viewed as a request for network upgrade driven by demands for innovative services, not only by demands for enhanced mobile networks per se. The R&D plan of the Korean government has been discordant with the vision of 5G, maintaining the tradition of sector- or issue-based R&D project support. This study proposed a strategic decision model for the 5G mobile industry, focusing on public R&D resource allocation, in response to the call for a revision of the ICT policy framework in Korea. The proposed model employed a criteriabased, quantitative, and comprehensive approach, using the AHP method, and an expert survey was conducted. The results showed that service platform is the critical layer that deserves priority in strategic public R&D resource input. Also, the ICT experts in Korea formed a consensus that upgrading physical networks per se is not the main driver of the next generation mobile industry, which verified the validity of the model.
Keywords: 330; 5G mobile; R&D; resource allocation; analytic hierarchy process; policy revision